Principles for additive manufacturing adoption and implementation by incumbent companies in emerging markets - Bitte, Mateus Frechiani (2024)
Industry 4.0 brings with it a series of technologies with great disruptive potential for organizations, which can revolutionize their products, services, production process and business model. The present study focused on one of these technologies, additive manufacturing (AM), or 3D printing. The goal of the technology is to transform digitally constructed objects into physical objects through printing on various materials. The literature has been highlighting the numerous advantages of technology and its possible disruptions in the day-to-day life of organizations, generating a hype around the topic. Despite the volume of literature, very little is known about the phenomenon and its real impacts on organizations and, therefore, the present study sought to understand in greater depth the phenomenon of adoption and implementation of additive manufacturing in established companies in the context of an emerging market. As the topic has not yet been explored, a principled approach is useful as it allows us to understand the journey of adoption and implementation of the technology as well as the causes of success or failure. To achieve the proposed objective, 3 case studies were carried out with established companies that adopted and implemented the technology in some of their processes. The analysis of the results allowed us to infer 10 critical principles for the successful adoption and implementation of the technology, as well as their interactions during the stages of the process. The three selected cases adopted the technology incrementally, seeking to improve existing processes in their organization, always looking for low-risk internal applications that do not affect the final delivery to the customer. The process began with the initiative of a member of the organization who saw value in the technology, identified use cases and developed pilot projects. This member, later in the cases studied, became the champion of the project that had a strong influence during the adoption and implementation process, seeking to convince the top management of the return that would be invested in the technology and bridging the gap between the internal and external environment of the organization. Non-industrial partnerships with knowledge centers and contact with material and technology suppliers were fundamental in the adoption and implementation, as well as in the evolution of the application of the technology in more complex uses. Despite the hype around the technology, it was possible to observe a low maturity of additive manufacturing in established organizations. Its use has not yet reached the products and services to the final customer, focusing on support activities such as maintenance, product development and tooling. No changes were observed in the capabilities set of organizations to operate with additive manufacturing, and these were used to improve existing capabilities. The three cases studied confirm a low level of technology maturity in companies established in the Brazilian context, however, there is a trend in the adoption of additive manufacturing for more critical processes in the future.